2022
DOI: 10.9734/ijpss/2022/v34i232531
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Planting Time on Yield and Quality of Spinach (Spinacia oleracea) Varieties

Abstract: The present investigation was conducted during rabi season of 2020 at Experimental Farm of Vegetable Sciences, Faculty of Agricultural Sciences, DAV University, Jalandhar to study the effect of different dates of sowing viz., 9 October, 24 October and 8 November and three cultivars, Supriya, All Green, Punjab Green on growth, yield and quality of spinach. The experiment was conducted in a Factorial Randomized Block Design with three replications. Observations were recorded on days to emergence, days to complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…than other transplanting dates. There is increased in leaf area with earlier planting with longer growing season due to maximal photosynthesis at longer growth period while in late sowing the growth decreased due to decrease in temperature at early stage causing cessation(Kaur et al, 2022). This result is in accordance with finding ofNaxrul and Zannat (2020) who reported that increase in leaf length (53.42 cm) and leaf width (23.99 cm) when sown on November 15.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…than other transplanting dates. There is increased in leaf area with earlier planting with longer growing season due to maximal photosynthesis at longer growth period while in late sowing the growth decreased due to decrease in temperature at early stage causing cessation(Kaur et al, 2022). This result is in accordance with finding ofNaxrul and Zannat (2020) who reported that increase in leaf length (53.42 cm) and leaf width (23.99 cm) when sown on November 15.…”
supporting
confidence: 89%
“…Significantly, highest leaf was recorded on second transplanting (November 9) of 28.92 t ha -1 . These results are due to the better germination and maximum photosynthesis surface (number of leaves per plant) in earlier sowing resulting to accumulation of maximum fresh weight as compared to late sowing (Kaur et al, 2022). Porter (2005) reported that late sown Indian mustard when exposed to high temperature and high atmospheric evaporative demands throughout the reproductive phase resulted in forced maturity, increased senescence and reduced output.…”
Section: Growth Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nepalese Journal of Statistics, Vol. 7, 1-18 K. R. Das, M. Jahan, L. R. Barman & P. Burman Barman analysis of variance technique was used in order to investigate the impact that planting time had on the production and freshness of spinach (Pathania et al, 2022). There is also some research done concerned with environmental issues.…”
Section: Introductionmentioning
confidence: 99%